ROOT ROTS, BUNT, POWDERY MILDEW AND RUST DISEASES OF WHEAT - Khakimova Nigora Takhirovna; Sattarova Rano Kadirovna (European Journal of Agricultural and Rural Education, 2024)
The article provides information about diseases of wheat plants, the genera of fungi that cause them, their distribution, the harm they cause, and the study of measures to combat them. This information is important for protecting wheat from diseases during the growing season and growing a high-quality crop from them